1993
DOI: 10.1161/01.str.24.8.1192
|View full text |Cite
|
Sign up to set email alerts
|

Rate of successful recording of blood flow signals in the middle cerebral artery using transcranial Doppler sonography.

Abstract: Background and Purpose: To assess the usefulness of transcranial Doppler sonography, we investigated the rate of blood flow signal recording failure in the middle cerebral artery in Japanese subjects. Furthermore, we studied the effect of increased emitted power on the rate of successful recording in some of the patients in whom recording failure had been detected at the standard transducer power of 100

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
91
1
9

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(110 citation statements)
references
References 10 publications
9
91
1
9
Order By: Relevance
“…3,4 A demonstration of improved rates of ACA visualization by using a combination of the TBW and FBW is important because the insonation quality of Japanese patients with stroke via the TBW is inferior, especially in the ACA territory. Sonographic contrast may be useful for the FBW, to improve detection rates as demonstrated in the TBW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 A demonstration of improved rates of ACA visualization by using a combination of the TBW and FBW is important because the insonation quality of Japanese patients with stroke via the TBW is inferior, especially in the ACA territory. Sonographic contrast may be useful for the FBW, to improve detection rates as demonstrated in the TBW.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In particular, an optimal TBW is difficult to apply in Asians. 3,4 Improving the detection rate of the anterior cerebral artery (ACA) by TCCS will increase the opportunity for such patients to undergo noninvasive and real-time evaluations at the bedside in general practice. In particular, Japanese patients will receive considerable benefits from an improved TCCS examination because pathologic changes often arise in the intracranial arteries, including the ACA.…”
mentioning
confidence: 99%
“…27) The low penetration rate of TCD (<10%) in this study was thought to reflect the fact that most of the Japanese neurointerventionalists were neurosurgeons 8) and that insonation through the temporal bone window was limited in elderly Asian (Japanese) people. 28) There were two institutes that performed the X-ray angiography perfusion analysis using the application that was bundled with their angiography equipment. Both Terada et al 29) and Fujimoto et al 30) have reported finding that the X-ray angiography perfusion analysis for detecting hyperperfusion after revascularization during CAS was effective, and thus, can be considered to be a promising modality for detecting hyperperfusion.…”
Section: Resultsmentioning
confidence: 99%
“…For a long time, because the acoustic temporal bone window is more restricted in the elderly, and notably in women, TCCS was usually carried out on patients aged under 55 years (Itoh, T. et al, 1993). Thanks to the use of contrast enhancement, the sensitivity and specificity of diagnostic ultrasound imaging have been considerably improved (Droste, et al, 2002).…”
Section: Tccs Examination Of the M1 Segment 31 General Proceduresmentioning
confidence: 99%